Teacher’s Strategies to Create a Conducive Learning Environment in The Ron Clark Story Movie - Yusuf, Adi; Pattisahusiwa, Ernawati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2020)
In learning process, a good teacher indeed needs a strategy to create a conducive learning environment in order that it runs smoothly. The Ron Clark Story Movie depicts how a teacher uses various strategies to create a conducive classroom environment so that the learning process can run well. The purposes of this research are to identify what strategies used by the teacher, Mr. Clark, to create a conducive learning environment in The Ron Clark Story Movie and to describe how the strategies are implemented by the teacher to create a condusive learning environment in the Movie. This study was designed qualitatively. The data of this study were scenes on the teacher’s strategies to create a conducive learning environment in the movie. The source of data in this study was a movie entitled The Ron Clark Story.It was found that Mr. Clark used 5 types of teacher’s strategies to create a conducive classroom environment: physical design of the classroom, rules and routines, relationship, engaging and motivation, and discipline. Each of the strategies has several classifications. By applying these strategies, the students of Mr. Clark finally succeeded in passing the exam with satisfactory grades.